Accreditation of medical laboratories in Republic of Macedonia - Tosheska Trajkovska, Katerina; Cekovska, Svetlana; Bosilkova, Gordana; Kostovska, Irena; Bogdanska, Jasna; Topuzovska, Sonja (Walter de Gruyter GmbH, 2017)
BACKGROUND: Accreditation of medical laboratories is a mark of quality and is objective proof that a laboratory is not only competent, but safe, patient-focused, efficient and reliable. ISO/IEC 15189:2012 is a globally recognized standard that specifies requirements for quality and competence particular to medical laboratories. It is for use by medical laboratories in developing their quality management systems and assessing their competence. METHOD/RESULTS: In a non-discriminatory manner, accreditation is accessible to every client submitting an accreditation application to the national Institute for accreditation. Quality systems in and accreditation of laboratories in our country are in varying phases of development. Some laboratories have established accreditation systems; others are still in the planning phase. Obtaining accreditation is still voluntary and there is poor participation of public sector laboratories. Till October 2016, four medical laboratories have been accredited according to MKS EN ISO/IEC 17025:2006 and five medical laboratories have been accredited according to MKC EN ISO 15189:2013. All accredited laboratories participate in EQAS concerning the analytical phase. A large proportion of errors occur in the pre-analytical phase and the problem is that the most EQA organizations do not offer pre-analytical EQA schemes. The rst step in improving the quality of the preanalytical phase is to describe potential errors and to try to estimate which errors are most dangerous for the outcome of the patient. Existing pre-analytical procedures should be compared to existing recommendations and thereafter improved to minimize the risk of errors. CONCLUSIONS: Development of a national standard as a starting standard for any country is one of the logical ways of implementing and initiating an accreditation programme. The standard may differ from one country to another depending on the state of development of the quality system in health laboratories. The national standard must be aligned with the international standard. In the case of medical laboratories, the aim of accreditation to ISO 15189 shall be the final target.
Keywords: accreditation; medical laboratories; EN ISO 15189:2012